Bilateral Giant Juvenile Fibroadenomas of Breasts:A Case Report. (30th May 2011) - Nikumbh, D. B.; Desai, S. R.; Madan, P. S.; Patil, N. J.; Wader, J. V.
Abstract : Juvenile fibroadenoma constitutes only 4% of the total fibroadenomas. The incidence of giant juvenile fibroadenomas is found to be only 0.5% of all the fibroadenomas. Bilateral giant juvenile fibroadenomas are extremely rare, and only four cases have been reported in the literature. To the best of our knowledge, we are presenting the fifth case of bilateral giant juvenile fibroadenomas in a 12-year-old prepubertal girl. The diagnosis was made on fine-needle aspiration cytology which was confirmed on histopathology. In this paper, we present this rare case to illustrate the diagnosis and management of this tumour and to emphasize that these tumours are almost always benign and should be treated with breast-conserving surgery to provide a healthy physical and social life to the patient.